Readiness Factors For AMT Implementation In Manufacturing SMEs - Ithnin, Hafini Suhana (2018)
Malaysia has been independent more than five decades since 1957. Along that way many changes and improvement had been experienced by Malaysian government and citizen. Since 1980 Malaysia had a big changes from agricultural sectors to industrial sectors. This great changing is consistent with world economic development and towards high income countries. Many activities and programs were planned to accomplish the goals. One of them is improving the production part. Implementation of Advanced Manufacturing Technologies (AMT) is the best strategy to speedy the production activities. For the large and established companies, this phenomena is not a big deal but for small organization especially for Small and Medium Enterprise (SMEs) many aspects need to be considered. Implementing AMT requires higher cost, risk and complexity. Although AMT are well known for long term profits but further research need to be done so that implementation is not futile. In this research, the researcher examined the relationship of readiness factors with AMT implementation within manufacturing SME. Other than that is to recognize the most influencing factor of implementing AMT in manufacturing SMEs. This research modified two domain theories which are Theory of Technology Index (TRI) and TOE Framework that analysed three independent variables (Individual Dimensions, Organization and Technology). Quantitative method was used for data collection that developed a set of questionnaire from previous literature review. Total of 120 questionnaire were distributed to manufacturing SMEs in southern of Malaysia. Results indicates that only two constructs had contributed significantly to the relationship with AMT implementation, which were innovativeness and technology favourability. This shown that presenting of these factors encourage AMT to be implement. Moreover, from these eight readiness factors, technology favourability shows the strongest impact towards AMT implementation. It can be proven that people are more interested to implement with new technology when they realize the benefits and suitability with the existing technology. This research indicates several theoretical implication and make several insights for development of manufacturing SMEs in Malaysia. For the view of managerial, this research provide an applicable framework that useful for AMT implementing. Subsequently, practical implication able to examine whether the SMEs are ready to implement AMT or not. Hence, an important implication of this study to the academics, policy maker and manufacturing practitioners in Malaysia is by creating knowledge on readiness factors to amend with better standard of manufacturing SMEs in Malaysia.